Design rules for carbazole derivatized n-alkyl methacrylate polymeric memristors. Issue 10 (26th February 2018) - McFarlane, Tucker M.; Zdyrko, Bogdan; Bandera, Yuriy; Worley, Deanna; Klep, Oleksandr; Jurča, Marek; Tonkin, Chip; Foulger, Stephen H.; Vilčáková, Jarmila; Sáha, Petr; Pfleger, Jiří
Abstract : The alternating current (AC) and direct current (DC) electrical response of a number of n -alkyl methacrylate polymers with a charge transporting pendant carbazole ring were studied. Abstract : The alternating current (AC) and direct current (DC) electrical response of a number of n -alkyl methacrylate polymers with a charge transporting pendant carbazole ring were studied. The electrical properties of the polymers were studied as a function of the n -alkyl length with n ranging from 2 to 11. The DC current ( I )–voltage ( V ) response of the polymers was characterized by an erratic and bistable response, while their AC I – V response was a pinched hysteresis loop when measured between 1–100 Hz. For polymers with n < 9, their pinched hysteresis loop was characterized by "jump transitions" indicative of bistability, while polymers with n ≥ 9 had a pinched hysteresis loop that was smooth in appearance. Dielectric spectroscopy on the polymers indicated that as the n -alkyl length is increased, the rotation flexibility of the carbazole moiety is enhanced. The n -alkyl methacrylate polymers with a pendant carbazole ring spaced n ≥ 9 exhibited a lower activation energy and temperature for the onset of ring motion and resulted in polymer-based memristors that exhibited electrical characteristics, such as incrementally adjustable conductivity and are potential candidates for mimicking synaptic plasticity.